The effect of quercetin delivery system on osteogenesis and angiogenesis under osteoporotic conditions. Issue 3 (23rd December 2016) - Zhou, Yuning; Wu, Yuqiong; Ma, Wudi; Jiang, Xinquan; Takemra, Akimichi; Uemura, Mamoru; Xia, Lunguo; Lin, Kaili; Xu, Yuanjin
Abstract : Bone regeneration under osteoporotic conditions with impaired angiogenesis, osteogenesis and remodeling represents a great challenge. Abstract : Bone regeneration under osteoporotic conditions with impaired angiogenesis, osteogenesis and remodeling represents a great challenge. In the present study, the effects of quercetin on proliferation, osteogenic differentiation and angiogenic factor secretion as well as on the osteoclastogenic factor secretion of ovariectomized (OVX) rat bone marrow-derived mesenchymal stem cells (rBMSCs) were first evaluated in vitro . The role of mitogen-activated protein kinase (MAPK) signaling pathways and the protein kinase B (AKT) signaling pathway in these processes was also investigated. Finally, hydroxyapatite (HA) bioceramic microspheres with a micro–nano hybrid surface (nHA bioceramic microspheres) were fabricated and used as drug delivery carriers of quercetin, and the ability to induce osteogenesis and angiogenesis in vivo was confirmed in an OVX rat critical-sized femur defect model. In vitro studies showed that quercetin significantly promoted cell proliferation, ALP activity and the expression of osteogenic and angiogenic factors of OVX rBMSCs as well as inhibited the expression of receptor activator of nuclear factor-κB ligand (RANKL) in a dose-dependent manner, with a concentration of 1 μM yielding the greatest effect. Moreover, the activation of the extracellular signal-regulated protein kinase (ERK), p38 and AKT signaling pathways was observed in quercetin-treated OVX rBMSCs, and the crosstalk among these signaling pathways was evident. Furthermore, the nHA bioceramic microspheres could efficiently release quercetin in a sustained manner, and quercetin loaded in the nHA bioceramic microspheres could promote new bone formation and blood vessel formation in vivo . The present study revealed that quercetin could promote osteogenesis and angiogenesis while inhibiting osteoclastogenesis both in vitro and in vivo under osteoporotic conditions. Moreover, HA bioceramic microspheres with a micro–nano hybrid surface could act as injectable drug delivery carriers of quercetin and could be applied for osteoporotic bone regeneration.